2020
DOI: 10.1523/jneurosci.2895-19.2020
|View full text |Cite
|
Sign up to set email alerts
|

RLN3/RXFP3 Signaling in the PVN Inhibits Magnocellular Neurons via M-like Current Activation and Contributes to Binge Eating Behavior

Abstract: Binge-eating disorder is the most common eating disorder. Various neuropeptides play important roles in the regulation of feeding behavior, including relaxin-3 (RLN3), which stimulates food intake in rats through the activation of the relaxin-family peptide-3 receptor (RXFP3). Here we demonstrate that a likely mechanism underlying the orexigenic action of RLN3 is RXFP3-mediated inhibition of oxytocin-and arginine-vasopressin-synthesizing paraventricular nucleus (PVN) magnocellular neurosecretory cells. Moreove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 68 publications
2
17
0
Order By: Relevance
“…A key finding of this study was that a small population of dopaminergic neurons within the ARC express RXFP3. It is therefore feasible, that RXFP3 activation inhibits this small proportion of ARC dopaminergic neurons, as electrophysiological studies suggest that postsynaptic RXFP3 signaling is predominantly inhibitory in rat and mouse ( Kania et al, 2017 ; Ch’ng et al, 2019 ; Kania et al, 2020 ). These data are in line with cell-based experiments demonstrating that RXFP3 activation reduces intracellular cAMP (see Kocan et al, 2014 for review).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A key finding of this study was that a small population of dopaminergic neurons within the ARC express RXFP3. It is therefore feasible, that RXFP3 activation inhibits this small proportion of ARC dopaminergic neurons, as electrophysiological studies suggest that postsynaptic RXFP3 signaling is predominantly inhibitory in rat and mouse ( Kania et al, 2017 ; Ch’ng et al, 2019 ; Kania et al, 2020 ). These data are in line with cell-based experiments demonstrating that RXFP3 activation reduces intracellular cAMP (see Kocan et al, 2014 for review).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, a previous study observed direct RXFP3-mediated inhibition of oxytocin and vasopressin neurons within the rat paraventricular hypothalamic nucleus (PVN) ( Kania et al, 2017 ). A recent follow-up study characterized these mechanisms further, and demonstrated that local PVN injection of an RXFP3 antagonist prevented binge eating in female rats ( Kania et al, 2020 ). The absence of tdTomato fluorescence within the PVN of RXFP3-Cre/tdTomato mice was therefore notable, particularly as previous in situ hybridisation studies have demonstrated high levels of Rxfp3 mRNA expression within this structure ( Smith et al, 2010 ; Ma et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another relevant aspect that remains to be assessed is how RXFP3 agonist activation modulates neuronal firing patterns within its different targeted areas. Electrophysiological studies in brain slices which focused on the hypothalamus and the bed nucleus of the stria terminalis demonstrated a reversible inhibition of neuronal firing (Kania et al, 2017 , 2020 ; Ch’ng et al, 2019 ).…”
Section: Relaxin-3/rxfp3 Signaling and Interference With Plastic Memomentioning
confidence: 99%
“…Using in situ hybridization techniques, compared to control (mice fed with low-fat diet) and obesity resistant mice, obesity prone mice had significantly higher levels of DRD4 mRNA expression in the ventral part of the lateral septal nucleus and ventromedial hypothalamic nucleus, suggesting a role for this receptor in the hypothalamic pathway [ 242 ]. Indeed, the DRD4, despite being predominantly expressed in the PFC, is also importantly localized in the hypothalamus [ 37 , 242 ], and it is well known that hypothalamic circuitries contribute to appetite control and energy homeostasis [ 243 , 244 , 245 , 246 , 247 ] by integrating a variety of neural inputs arising from both neuropeptides and neurotransmitters [ 248 , 249 , 250 , 251 , 252 , 253 , 254 , 255 ] and modulating the mechanisms underlying ingestive behavior and stress [ 256 , 257 , 258 ]. These findings suggest that the DRD4 may influence food intake and eating behaviors at the level of both the PFC, as previously discussed, and the hypothalamus.…”
Section: Drd4 and Feeding Behaviormentioning
confidence: 99%